Hoslundia opposita vahl (Lamiaceae) leaves, chemosensitivity evaluation on plasmodium falciparum - OBOU CONSTANTIN OKOU; SYLVAIN BEOUROU; ALLOH ALBERT GNONDJUI; EVE VICTOIRE AKPOUE; ALLICO JOSEPH DJAMAN (International Journal of Pharma and Bio Sciences, 2019)
Malaria remains a public health problem because of the consequences it has. Existing treatments are becoming increasingly ineffective. It is therefore urgent to find new antimalarial drugs. Medicinal plants appear to be an important source to explore. Thus, this study on Hoslundia opposita will provide a scientific basis for its traditional use. Indeed, Hoslundia opposita has always been used in traditional medicine by naturopaths for the treatment of malaria. This study is part of a vast program of extensive medicinal plant science. The objective of this work is to evaluate in vitro chemosensitivity of the aqueous and hydroethanolic extracts of Hoslundia opposita (Lamiaceae) leaves on Plasmodium falciparum by maturation tests and RSA ex vivo. The maturation test of the different extracts from the five clinical isolates of Plasmodium falciparum showed antimalarial activity, with a promising effect of the aqueous extract (IC50 = 12.66 μg/mL). The two extracts obtained by hydroethanolic partition have a moderate effect with IC50 between 15 and 50 μg/mL. The results of the RSA ex vivo test confirmed those of the maturation test with a survival percentage of approximately 50% of parasites (i,e 50% inhibition), as the parasites were exposed to the IC50 of the various cells extracts used for the maturation test. These results make Hoslundia opposita a potential resource in the search for antimalarial molecules.